Ameaças à Infância: do Trauma Psíquico ao Transtorno de Estresse Pós-Traumático - Silva, Flávia Cristina Amaro da (2006)
This research is the result of the master s degree dissertation in Clinical Psychology in the Psychosomatic Department and Hospital Psychology of PUC-SP, with theorical reference to the psychoanalitic theory. The study had, as a first objective, the literature revision of the posttraumatic stress disorder (PTSD) in children; as second, the literature revision in the psychodinamic of the trauma experience in the psychoanalitic clinic, and as the third objective, the apprehension of the posttraumatic stress disorder (PTSD) clinical presentation with the psychodinamic of the trauma experience. For the first revision, the data bases Pubmed, Medline, Lilacs and Pilots were used. For the second, it was used database entailed Psique to the library of the São Paulo s Institute of the Brazilian Psychoanalysis Society. The study includes the posttraumatic stress disorder (PTSD) aspects in children with an illness or a potentially serious, acute or chronic, medical condition and studies about the trauma subjective experience in the psychoanalitic theory involving the sick children. The studies with children excluded those who were victims of automobile trauma. The apprehension of the PTSD from the psychodinamic theory was based on elements of S. Freud, S. Ferenczi and D. W. Winnicott s theories. The results, as well as the discussion, had demonstrated a Brazilian publication scarcity in the area. They had evidenced the joint and apprehension of the PTSD with the trauma psychoanalitic psychodinamic. It was possible to verify the serious disease traumatic potential in infancy and the damages that it can cause in the biological, psychic and social development, when the child cannot give a meaning to her experiences in her representation system. Steady care and social support can act as protection factors, favoring a growth posttraumatic stress situation. Finally, it has been considered that the health professionals whom directly deal with these children have an important paper to brighten up the stressing effects of these experiences, as well as the psychoanalitic psycotherapy can offer a accompaniment for the child in the confrontation with the irrepresentable.